Gastroesophageal Reflux Disease and Tooth Erosion - Sarbin Ranjitkar; John A. Kaidonis; Roger J. Smales (Hindawi Limited, 2012)
The increasing prevalence of gastroesophageal reflux disease (GERD) in children and adults, and of "silent refluxers" in particular, increases the responsibility of dentists to be alert to this potentially severe condition when observing unexplained instances of tooth erosion. Although gastroesophageal reflux is a normal physiologic occurrence, excessive gastric and duodenal regurgitation combined with a decrease in normal protective mechanisms, including an adequate production of saliva, may result in many esophageal and extraesophageal adverse conditions. Sleep-related GERD is particularly insidious as the supine position enhances the proximal migration of gastric contents, and normal saliva production is much reduced. Gastric acid will displace saliva easily from tooth surfaces, and proteolytic pepsin will remove protective dental pellicle. Though increasing evidence of associations between GERD and tooth erosion has been shown in both animal and human studies, relatively few clinical studies have been carried out under controlled trial conditions. Suspicion of an endogenous source of acid being associated with observed tooth erosion requires medical referral and management of the patient as the primary method for its prevention and control.